Diagnosis of gestational diabetes: a 'teachable moment'. Issue 2 (3rd September 2018) - Okely, J.; Mason, C.; Collier, A.; Dunnachie, N.; Swanson, V.
Abstract: Aims: Research regarding the determinants of concordance with gestational diabetes mellitus (GDM) treatment is limited. Here, we test whether the psychosocial changes outlined in the teachable moments model, as proposed by McBride et al . (McBride CM, Emmons KM, Lipkus IM. Understanding the potential of teachable moments: the case of smoking cessation. Health Educ Res 2003;18 : 156–170) are associated with following GDM treatment recommendations. Methods: Fifty‐nine women completed a baseline questionnaire (1 week after GDM diagnosis) in which they reported risk perception, social support, emotional response, the importance of their maternal identity and self‐efficacy. One month later, participants reported their concordance with instructions regarding glucose monitoring, diet and, if applicable, medication. We used regression analysis to test for associations between the psychosocial factors measured at baseline and concordance at 1‐month follow‐up. Results: Those who perceived their risk as higher or felt supported by family or friends were more likely to report a high level of concordance with GDM treatment. Emotional response, identity salience and self‐efficacy were not related to concordance. Conclusions: Future interventions designed to increase concordance could benefit from a focus on risk perception and social support, as these factors appear to be most strongly associated with following GDM treatment recommendations. What's new?: Research regarding the determinants of effective gestational diabetes mellitus (GDM) self‐management is limited. We tested whether the psychosocial changes outlined in the teachable moments model (a model of behaviour change) are associated with following GDM management recommendations during pregnancy. Higher perceived risk of complications during pregnancy and feeling supported by family or friends was associated with higher levels of concordance with GDM management recommendations.